Network isolation communication scheme to resist against covert channel - Feng-hua LI; Miao-miao TAN; Kai FAN; Kui GENG; Fu ZHAO (Tongxin xuebao)
With the rapid development of network technologies，real-time information exchanging between heterogeneous networks becomes more frequently.To effectively guarantee the secure and real-time information exchanging crossing different networks，a network isolation communication scheme (NICS) is proposed to resist against covert channel.A newly theoretical model of NICS is designed and proved based on the information theory，and followed with a specific solution.Security analysis indicates that the NICS is able to effectively solve problems of the potential packet lengths’ covert channel (PLCC) and the status covert channel (SCC) in most of the existing work; and，given similar amount of information for exchanging，the NICS can achieve equivalent security degree with the physical isolation in terms of resisting against the covert channel.